پاراستنی بەرژەوەنیدیەکان لە هێندستان لە رێکەوتننامەی سایکس– پیکۆ وەک گرنگترین بەربەست لە دروستبونی دەوڵەتی کوردی - محمد, ئه‌دهه‌م ره‌مه‌زان (Sulaimani Journal for Humanities, 2018)
Abstract Kurdistan, the region which its population are Kurdish people, which has been divided according to the Zahaw treaty in 1639 between the Safavid and Ottoman Empire. After the end of the WW1, the first reign of the Ottoman the biggest part of the Kurdistan fell apart, according to the Sykes-Picot agreement which was signed in the middle of the war for the benefit of those countries which won the war, many independent states within the Ottoman Empire are established. However, Kurdistan region in general and specifically the Kurdish region within Ottoman empire, was not only being acknowledged as an independent nation but It become the victim for those winner nations especially Britain, at the end of the War , Kurdistan was divided and given to three countries (Iraq, Syria, Turkey) . This research depending on the historical methodological analysis, throughout detailed reading and analyzing the historical data, attempts to investigate the effect of high beneficiary by the winner nations on the Kurdistan population. The result of the study shows that the main interests for the Britain was; Britain found itself as the major liberator of India, which was the biggest colonial at that time. This in a way had the major role in drafting the border or map of the region according to the Sykes-Picot agreement and the influence of the Russia and France in the next place after Britain.